Reassembling the Pimped Ride: A Quantitative Look at the Integration of a Borrowed Expression - De Pascale, Stefano; Pijpops, Dirk; Van de Velde, Freek; Zenner, Eline (Frontiers in Communication, 2022)
Over the past decades, research on the linguistic impact of globalization has foregrounded the socio-pragmatic meaning potential and mental categorization of anglicisms, looking for signs of agentivity and contextual sensitivity in the way receptor language users incorporate borrowed English resources into their speech, both in form and in function. This brought attention to understudied phenotypes of contact-induced variation and change that go beyond the borrowing of individual lexical items (loanwords) from English. This paper aims to contribute to this endeavor, illustrating the potential of construction grammar to uncover the integration of borrowed chunks. In focus is the emergence of the verb "pimpen" ‘to pimp’ in Dutch, a rapid innovation from the English proper name "Pimp my Ride". A sample of 4,561 Dutch tweets containing (strings of) "pimp" posted between January 2007 and April 2020 was coded manually for formal and semantic properties. This allowed us to calculate an aggregate score of ‘deconstructionalization’ both within and outside of the target construction [pimp POSS N]. Results indeed reveal a gradual blurring of the sharp contours of the construction, but also indicate that this process mainly affects the instantiations closest to the original. Linked up with the mediatized origin of the construction, our results add to our understanding of the relationship between media, language contact, and what is referred to as glocalization.